(untitled) (Journal of Science and Technology, 2016)
The strength of a square plate under a diagonally compressive load is experimentally examined using a photoelastic method and some optical laws. Lame-Maxwell equations coupled with Filon’s transformation, which in essence is a graphical approach, is utilized to separate and interpret the principal stresses. This, of course, is a very powerful method for verifying analytic solutions and also a method for solutions to other complex problems in stress analysis. Many structural loadings of plate serving as columns or structural systems, such as ship and aero-plane structures; shell structures and blades of static and dynamic mechanical equipment with notches, cracks or irregular edges or shapes must have their structural response or behaviour properly predetermined for engineering design irrespective of the existing design code. This technique is very important in obtaining the stress trajectory and it is comparatively simple and less expensive than the usual sophisticated finite element approach that is also capable of producing a similar strength trajectory.